Hubungan Kualitas Tidur DenThe Relationship Between Sleep Quality and Learning Concentration of Grade VIII Students at SMP Negeri 4, Bogor Citygan Konsentrasi Belajar Siswa Kelas Viii Di Smp Negeri 4 Kota Bogor - Najwa Nabila Putri (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
Learning concentration is an important aspect that determines students’ success in understanding learning materials. Good concentration enables students to focus their attention on the learning process so that learning objectives can be achieved optimally. One factor presumed to be associated with learning concentration is sleep quality. Good sleep quality plays a role in maintaining cognitive function, memory, and the ability to focus attention. This study aimed to determine the description of sleep quality, learning concentration, and the relationship between sleep quality and learning concentration among eighth-grade students of SMP Negeri 4 Kota Bogor. This study employed a quantitative approach using a correlational method. The population consisted of 351 eighth-grade students, with a sample of 187 students selected through simple random sampling. The instruments used were the Pittsburgh Sleep Quality Index (PSQI) and a learning concentration questionnaire. Data were analyzed using Spearman Rank correlation with SPSS Statistics 25. The results showed that 105 students (56.1%) had poor sleep quality and 82 students (43.9%) had good sleep quality. Meanwhile, 100 students (53.5%) had high learning concentration and 87 students (46.5%) had low learning concentration. The Spearman Rank correlation test showed a correlation coefficient of 0.003 and a significance value of 0.968 (p>0.05). Therefore, there was no significant relationship between sleep quality and learning concentration among eighth-grade students of SMP Negeri 4 Kota Bogor.